Mechanism and Controlling Factors on Methane Yields Catalytically Generated From Low-Mature Source Rocks at Low Temperatures (60–140°C) in Laboratory and Sedimentary Basins - Wei, Lin; Yin, Jia; Li, Jiansheng; Zhang, Kun; Li, Chunzhen; Cheng, Xiong (Frontiers in Earth Science, 2022)
Various studies have shown that geo-catalytically mediated methanogenesis could happen in immature to early mature source rocks at temperatures from 60 to 140 ℃ based on series long term laboratory heating experimental evidences. However, different types of source rocks in these laboratory simulation experiments generated varied CH4 and CO2 yields, which suggests that controls on CH4 generation during catalytic methanogenesis are complex. This study summarizes and compares gas yield results from laboratory low temperature heating simulation experiments. Pre-existing trapped methane in rock chips could mimic newly generated gas during heating. The yields of catalytically generated CH4 from individual source rocks were re-quantified by subtracting the amounts of pre-existing CH4 in the closed pores of the original source rocks from the total methane amounts of released from heating experiment and pre-existing CH4 in the closed pores in heated source rocks. The results show that heating temperature and time exerts certain influence on methane catalytic methanogenesis. Mowry and Second White Specks Formation Shale generated approximately 10 times more CH4 than New Albany Shale and Mahogany Shale per g of TOC. Samples of Springfield Coal #1 and #2 exhibit 10 times yield difference from one another at the same heating temperature. Those yield differences are not strongly associated with TOC content, heating time, temperature or kerogen type but appear to be influenced by maceral composition and also maceral-mineral contact area within the source rocks. We conclude that macerals in the liptinite group have propensity for methanogenesis. Specifically, amorphous organic matter undergoes transformation into hydrocarbons earlier than alginite at low temperature heating condition. Sporinite also contributes to higher yields of methane released from the coal source rock. Vitrinite and inertinite show positive influence on carbon dioxide but no significant effect on increasing methane yields compared to other macerals. Strongest catalytic methanogenesis in studied sample produced methane yields at 60 °C amounted to ~2.5 μmol per gram of organic carbon during one year heating. We suggest that the geocatalytic methanogenesis could generate economically sizeable gas plays from immature to early mature source rocks over geologic time.